Chemical characteristics and deposition amounts of carbonaceous species and inorganic ions in precipitation in the Bangkok Metropolitan Region. (15th December 2022) - Huo, Mingqun; Sato, Keiichi; Kim Oanh, Nguyen Thi; Mettasitthikorn, Metta; Leamlaem, Malulee; Permadi, Didin Agustian; Narita, Daiju; Garivait, Hathairatana; Laogul, Wanna; Akimoto, Hajime
Abstract: A comprehensive study on the chemical characteristics and deposition fluxes of precipitation components, including water-insoluble organic carbon (WIOC), water-soluble organic carbon (WSOC), and elemental carbon (EC), including Char-EC and Soot-EC, and major inorganic ions, was conducted from September 2015 to March 2017 at suburban (AIT) and urban (PCD) sites in the Bangkok Metropolitan Region (BMR), Thailand. This is the first study of this kind conducted in tropical areas. To study the scavenging effect of atmospheric particles by wet deposition, atmospheric particulate carbonaceous components were simultaneously measured. The average concentrations of carbonaceous components in precipitation were higher at AIT than at PCD (Bangkok City Center). The contribution of WIOC to total organic carbon (OC) in precipitation was more important at AIT than at PCD sites, whereas the opposite was observed for the contribution of EC. The concentrations of all components in precipitation during the dry season were higher than those during the wet season. The washout processes efficiently removed atmospheric carbonaceous components in the study area, a tropical urban region with a high atmospheric particle concentration. The scavenging ratios (SRs) followed the order of main anthropogenic ions (NO3 − and SO4 2− ) > OC > Soot-EC > Char-EC. The annual mean SRs of NO3 −, SO4 2−, OC, Soot-EC, and Char-EC were 1.61, 1.13, 0.75, 0.09, and 0.03 at AIT and 0.96, 1.04, 0.63, 0.08, and 0.03 at PCD, respectively. The washout process was dominant for water-insoluble components (EC and WIOC), whereas the rain-out process was relatively more prominent for water-soluble components (WSOC, SO4 2− and NO3 − ). The wet deposition amounts of carbonaceous and main inorganic anions ranked in the order of NO3 − > WSOC> SO4 2−  >WIOC>EC, suggesting that the influence of secondary particles was more significant than that of the primary particles. The volume-weighted average pH values of rainwater at suburban and urban sites were 6.25 and 6.04, respectively. NO3 − was observed to play a relatively more important role than SO4 2− in the acidity of rainwater in the BMR. The acidity in the precipitation was almost neutralized by the alkalinity. Highlights: First study on simultaneous monitoring of carbonaceous fractions in precipitation and particles in Southeast Asia. The scavenging ratios followed the order of inorganic ions (NO3 − and SO4 2− ) > OC > Soot-EC > Char-EC. The slope coefficients between rainfall amount and precipitation concentration were evaluated.